A Medal in the Olympics Runs in the Family: A Cohort Study of Performance Heritability in the Games History - Antero, Juliana; Saulière, Guillaume; Marck, Adrien; Toussaint, Jean-François (Frontiers in Physiology, 2018)
Elite performance in sports is known to be influenced by heritable components, but the magnitude of such an influence has never been quantified. Hypothesis/Objectives: We hypothesized that having a former world-class champion in the family increases the chances of an athlete to repeat the achievement of her or his kinship. We aimed to measure the heritability of a medal in the Olympic Games (OG) among Olympians and to estimate the percentage of the genetic contribution to such a heritance. Study Design: Twin-family study of a retrospective cohort. Methods: All the 125,051 worldwide athletes that have participated in the OG between 1896 and 2012 were included. The expected probability to win a medal in the OG was defined as the frequency of medallists among Olympians without any blood kinship in the OG. This expected probability was compared with the probability to win a medal for Olympians having a kinship (grandparent, aunt/uncle, parent or siblings) with a former Olympian that was a 1) Non-medallist or 2) Medallist. The heritability of the genetically-determined phenotype (h2) was assessed by probandwise concordance rates among dizygotic (DZ) and monozygotic (MZ) twins (n = 90). Results: The expected probability to win a medal in the OG was 20.4%. No significant difference of medal probability was found in the subgroups of Olympians with a Non-medallist kinship, except among siblings for whom this probability was lower: 13.3%, (95% CI 11.2 to 14.8). The medal probability was significantly greater among Olympians having a kinship with a former Olympic Medallist: 44.4% for niece/nephew (33.7 to 54.2); 43.4% for offspring (37.4 to 48.6); 64.8% for siblings (61.2 to 68.8); 75.5% for DZ twins (63.3 to 86.6); and 85.7% for MZ twins (63.6 to 96.9); with significantly greater concordance between MZ than DZ (p = 0.01) and h2 estimated at 20.5%. Conclusions: Having a kinship with a former Olympic medallist is associated with a greater probability for an Olympian to also become a medallist, the closer an athlete is genetically to such kinship the greater this probability. Once in the OG, the genetic contribution to win a medal is estimated to be 20.5%.